Building the Next Bioethics Commission. (May 2017) - Capron, Alexander M.
Abstract: At every moment, somewhere in the world, a group of men and women are sitting around a table deliberating about an ethical issue posed by medicine and research, whether as a research ethics committee; a hospital or clinical ethics committee; a stem‐cell review committee; a gene transfer research committee; a biobank ethics committee; an ethics advisory committee for a medical or nursing association or nongovernmental organization; a state, provincial, national, or intergovernmental bioethics committee; or an ad hoc panel examining a particular development or case. However, the last national committee in the United States, the Presidential Commission for the Study of Bioethical Issues, held its final meeting at the end of August 2016 and closed its doors. Should we regret its departure? I believe that the United States would benefit from having another national bioethics advisory body, but I do not think that the commission should simply have continued under a new president in the same form. Instead, looking at the experience of that commission and its six predecessors—who they were, how they worked, the functions they served, and the problems they experienced—we can derive some useful ideas for anyone planning to build the next commission .